Using Video Modeling to Teach Geometry Word Problems: A Strategy for Students With Learning Disabilities - Satsangi, Rajiv; Hammer, Rachel; Bouck, Emily C. (Remedial and special education, 2020)
As K-12 mathematics standards shift toward emphasizing both conceptual and procedural knowledge in secondary courses such as algebra and geometry, the struggles for students with disabilities become more pronounced. To address these challenges, research has commonly explored the use of technology to aid in the teaching of students with disabilities. One such technology with a growing research base for instruction in the field of special education is the use of video modeling. Despite documented success for students with moderate to severe disabilities, the application of video modeling for instruction with students with a learning disability is largely unknown. This study sought to explore the benefits of video modeling to teach geometry word problems to three secondary students with a learning disability in mathematics. Across a single subject multiple baseline design, all three students demonstrated improved problem-solving performance across all dependent variables measured. The results and their implications for the field of mathematics are discussed.